Marketing in the digital age - Kumar, Dinesh (Sage, 2021)
"This textbook describes how digital methods can enhance marketing experience going beyond cliched metrics of likes and shares in digital marketing strategies. Marketing in the Digital Age takes the view that the path to the future must integrate both marketing and digital knowhow and exemplifies how digital marketing is more than just spreading the message using digital tools. A path-breaking textbook for students who wish to understand marketing in a rapidly changing environment, this book offers a fresh approach towards all the core areas of marketing, including segmentation, product development, promotion, pricing, going to the market and relationship building. Key Features: Offers conceptual clarity and refreshing treatment of use of digital tools in marketing; Encourages the readers to adopt a critical approach to standard aspects of marketing and traditional notions of use of the digital in businesses; Each chapter comes with a plethora of exhibits and case studies, from India and abroad Rich pedagogical features to aid teaching-learning in the classroom - learning objectives, chapter-end summary, glossary terms, concept-review and critical thinking questions, ideas for projects and group assignments, and much more"--